The Role of Strategic Partnerships in Organizational Success: A Case Study of a Men’s Clothing Factory in Najaf: Peran Kemitraan Strategis dalam Kesuksesan Organisasi: Studi Kasus Pabrik Pakaian Pria di Najaf - AL-Janabi, Mohanad Abdulabbas Jasim (Universitas Muhammadiyah Sidoarjo, 2025)
This study investigates the role of strategic partnerships in enhancing organizational success within a men’s clothing factory in Najaf Al-Ashraf, Iraq. Using a quantitative approach, 85 questionnaires were distributed to a random sample of employees, of which 80 were valid and suitable for analysis. Data were analyzed using SPSS v.26 and AMOS v.26 to examine the relationship between strategic partnerships, considering their key dimensions and organizational success. The results reveal a strong and statistically significant positive correlation between strategic partnerships and organizational success. Findings indicate that strategic partnerships significantly contribute to improved performance, operational efficiency, innovation, and overall achievement of organizational goals within the factory setting. The study concludes that fostering strategic partnerships is a critical factor in driving success in the men’s clothing manufacturing sector in Najaf Al-Ashraf. A key recommendation is for the factory to prioritize and actively develop strategic partnerships with suppliers, distributors, design collaborators, and other industry stakeholders to sustain long-term growth and competitiveness.